Protocol for process evaluation of a randomised controlled trial of family-led rehabilitation post stroke (ATTEND) in India - Liu, Hueiming; Lindley, Richard; Alim, Mohammed; Felix, Cynthia; Gandhi, Dorcas B.C.; Verma, Schweta J.; Tugnawat, Deepak Kumar; Syrigapu, Anuradha; Ramamurthy, Ramaprabhu Krishnappa; Pandian, Jeyaraj D.; Walker, Marion F.; Forster, Anne; et al. (BMJ Publishing Group, 2016)
Introduction We are undertaking a randomised controlled trial (fAmily led rehabiliTaTion aftEr stroke in INDia, ATTEND) evaluating training a family carer to enable maximal rehabilitation of patients with stroke-related disability; as a potentially affordable, culturally acceptable and effective intervention for use in India. A process evaluation is needed to understand how and why this complex intervention may be effective, and to capture important barriers and facilitators to its implementation. We describe the protocol for our process evaluation to encourage the development of in-process evaluation methodology and transparency in reporting.